Interlaminar damage detection in composite elements by means of optical fibre sensors - Bettini, P.; Airoldi, A.; Bogotto, P.; Loutas, T. (My University, 2017)
The interest of aerospace industry about SHM is continuously increasing and many studies are conducted to develop new reliable techniques. Monitoring the health of a structure is essential to prevent failure and improve maintenance activities. This work is aimed at assessing the capability of detecting the outliers originated by interlaminar damages in a relatively bulk composite element, which is a representative component of modern composite structural solution. At first, manufacturing activities are presented with particular attention to the technological issues related to the integration of FO sensors inside laminates. DTG (Draw Tower Gratings) arrays with a configuration reproducing long chirped sensors are embedded and located near three different artificial delaminations. A reference undamaged zone is also monitored in the same way. By using a numerical model of DTGs capable of simulating their acquired spectral response, a new originally developed code is adopted to retrieve the strain field applied along gauge section. Position and size of sensors network and defects are designed by means of a FE analysis of the composite component. Changes in the strain field due to the presence of the defects are evidenced, highlighted, and evaluated by comparing such strain field with the reference one both in numerical models and experiments.